LAST YEAR UNIVERSITY STUDENTS’ MOTIVES FOR LEARNING AND THE WAYS TO INCREASE THEIR MOTIVATION - Jermolajeva, Jelena; Silchenkova, Svetlana; Turusheva, Larissa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Monitoring and analysing the students’ academic motivation allows the university teacher to look at the results of her/his work from another aspect and reflect on the ways of increasing the effectiveness of teaching. The aim of the study is to analyse and compare the groups of the learning motives of last year students at the Universities of Riga (EKA University of Applied Sciences) and Smolensk (Smolensk State University), on the basis of which propose the ways to increase their motivation. In the international survey, which was carried out in December 2018 – June 2019, 101 students participated. Descriptive statistics was used for the data processing. Data analysis shows that in both samples the group of professional motives plays a leading role in the students’ learning motivation. In Latvia, the second and third places are to communication and creative self-realisation motives, in the Smolensk sample – social and communication motives, respectively. The results of the study can be used by university teachers and study programme directors for improving the management of education and raising the quality of the pedagogical process.